Health Care Provider Utilization of Prescription Monitoring Programs: A Systematic Review and Meta-Analysis. Issue 7 (23rd January 2021) - Robinson, Alysia; Wilson, Maria N; Hayden, Jill A; Rhodes, Emily; Campbell, Samuel; MacDougall, Peter; Asbridge, Mark
Abstract: Objective: To synthesize the literature on the proportion of health care providers who access and use prescription monitoring program data in their practice, as well as associated barriers to the use of such data. Design: We performed a systematic review using a standard systematic review method with meta-analysis and qualitative meta-summary. We included full-published peer-reviewed reports of study data, as well as theses and dissertations. Methods: We identified relevant quantitative and qualitative studies. We synthesized outcomes related to prescription monitoring program data use (i.e., ever used, frequency of use). We pooled the proportion of health care providers who had ever used prescription monitoring program data by using random effects models, and we used meta-summary methodology to identify prescription monitoring program use barriers. Results: Fifty-three studies were included in our review, all from the United States. Of these, 46 reported on prescription monitoring program use and 32 reported on barriers. The pooled proportion of health care providers who had ever used prescription monitoring program data was 0.57 (95% confidence interval: 0.48–0.66). Common barriers to prescription monitoring program data use included time constraints and administrative burdens, low perceived value of prescription monitoring program data, and problems with prescription monitoring program system usability. Conclusions: Our study found that health care providers underutilize prescription monitoring program data and that many barriers exist to prescription monitoring program data use.